Design and characterization of multifaceted lyophilized liposomal wafers with promising wound healing potential - Avachat, Amelia M.; Takudage, Pooja J. (Journal of liposome research, 2018)
Various dressings are available to heal chronic wounds which many times fail to achieve the expected results. To overcome some of their drawbacks, formulation of a novel dressing; lyophilized liposomal wafers having better wound healing potential has been proposed in the present study. The drug incorporated in the formulation is gatifloxacin (GTX) which is a fourth-generation fluoroquinolone antibiotic having in vitro activity against both Gram-negative and Gram-positive bacteria. The formulation was designed in three stages where at first liposomes were prepared, the liposomes were converted to gel using chitosan and lastly this gel was lyophilized to form liposomal wafers. Liposomes were prepared by varying the concentration of lipid and cholesterol and evaluated for particle size, entrapment efficiency, in vitro cumulative release, transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Liposomes were converted to liposomal gel using chitosan and evaluated for texture, clarity, viscosity, spreadibility and in vitro drug release. Finally, this liposomal batch was subjected to lyophilization to convert it to liposomal wafers and subjected to SEM, differential scanning calorimetric, X-ray diffraction and drug release studies. The in vivo studies were carried out on Wistar rats where wound healing potential of the wafers was confirmed by histopathological evaluation.